2021
DOI: 10.11648/j.jps.20210904.23
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Farmers’ Perceptions, Preferences and Utilization Patterns of Taro [<i>Colocasia esculenta</i> (L.) Scott] for Food and Nutrition Security in Nigeria

Abstract: Malnutrition afflicts a large number of people in Sub-Saharan Africa. Orphan crops, such as Taro plants, can play critical roles in ensuring global food and nutritional security in this regard. Nigeria is the world's leading producer of taro. It is primarily consumed as a main component or as a soup thickener by resource-poor rural residents in Nigeria's south-eastern regions. The corm contains a lot of carbohydrates, while the leaves have a lot of protein. Furthermore, its social and medicinal importance shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Higher moisture levels contribute to a softer and more delicate texture, which can be desirable in specific culinary applications. However, these conditions also increase the risk of microbial growth and enzymatic activities, leading to spoilage and a decline in quality over time [28]. Taro and other edible aroids are challenging to store and transport due to their bulk and vulnerability to physical damage, which allows microbes to invade and cause decay in the interior starchy tissues [4].…”
Section: Moisture Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher moisture levels contribute to a softer and more delicate texture, which can be desirable in specific culinary applications. However, these conditions also increase the risk of microbial growth and enzymatic activities, leading to spoilage and a decline in quality over time [28]. Taro and other edible aroids are challenging to store and transport due to their bulk and vulnerability to physical damage, which allows microbes to invade and cause decay in the interior starchy tissues [4].…”
Section: Moisture Contentmentioning
confidence: 99%
“…Excessive moisture loss during storage or transportation results in weight reduction and physical damage, which results in economic losses for producers and suppliers. Hence, optimizing storage conditions and implementing appropriate handling practices are crucial to maintaining the taro's moisture content and maximizing its market value [28].…”
Section: Moisture Contentmentioning
confidence: 99%
“…TLB outbreak resulted in a drastic reduction in production level and farmland size in the southern part of Benin. It has been reported that taro is affected by many diseases and pests in many places of the world (Ayogu et al, 2015), especially P. colocasiae (Sarkar et al, 2017;Wondimu et al, 2021). This disease, which is the most devastating, caused economic losses of more than US$1.4 billion during the TLB pandemic and significantly impacted the genetic diversity of the local gene pool of the plant (Onyeka, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although taro is highly valued, its production is affected by several biotic and abiotic constraints. Taro Leaf Blight (TLB), caused by Phytophthora colocasiae Raciborski, is a major taro disease, responsible for about 50 to 95% of the loss of taro production (Otieno, 2020;Wondimu et al, 2021). The disease was first observed in West Africa in 2008 to 2009 and led to a 60% decline in the production in several countries (Bandyopadhyay et al, 2011;Omane et al, 2012;Tsopmbeng et al, 2012;Mbong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moisture content plays a significant role in the proximate analysis of taro tubers. A lower moisture content (< 80 %) is helpful for transport and storage of corms at ambient temperatures (Wondimu Fufa et al, 2021;Ferdaus et al, 2023).…”
Section: Moisture (%)mentioning
confidence: 99%